Pengaruh Literasi Keuangan, Pemanfaatan Teknologi Informasi dan Inovasi Terhadap Kinerja Usaha Mikro Kecil Menengah (UMKM) Di Kecamatan Buleleng - Andini, Novia Dwi; Wati, Ni Wayan Alit Erlina; W, Rai Dwi Andayani (UNHI Press, 2025)
The current performance of MSMEs can stimulate the economy, especially in Bali, to increase, one of whichs is the high literacy of MSME managers about finance, being able to makes the best usse of informations technology and having interesting innovations so as to improve the performances of MSMEs. Thes aim of thiss ressearch is to determines the inflluence of financials literacy, use of informatiosn technologys and innovation ons the performances of Micros, Small and Medium Enterprises in Buleleng District. The number of samples required for this research is 96 respondents. The techniques ussed in determininsg this sample is Random Sampling. The data collections method in this ressearch is a questionnaire technique. The analyssis technique uses multiples linear regression analyssis. The results of this research are 1) Financial literacy influences MSME performances variables. This means that if financiall literacy increases, the performances of Micros, Small and Medium Enterprisses (MSMEs) in Buleleng District will also increase. 2) The usse of information technology influences the performances of MSMEs. This means thats the increasing usse of informations technologys can improve the performances of Micrso, Small and Medium Enterprisses (MSMEs) in Buleleng District. 3) Innovation influences the performances of MSMEs. This means that the higsher the innovation, the more Micros, Small and Medium Enterprisses (MSMEs) in Buleleng District can improve. The advice given is to use the SIAPIK application which functions as a digital financial recording application which can makes it easier for MSMEs to records their bussiness financial transactions without needing to understand accounting rules and sell MSME products through e-commerce such as Shoppe or Tokopedia, making it easier for employees to market MSME products.